2022-RA-1046-ESGO Frequency of bowel anastomosis leakage after modified posterior exenteration – comparison of two surgical Methods: classic surgery in patients with ovarian cancer and minimal invasive modified 'tailored' technique in deep infiltrating endometriosis patients. (20th October 2022) - Kasperski, Mariusz; Nowak, Krzysztof; Mrugała, Maja; Kalus, Marcin; Nabzdyk, Ewa Milnerowicz –
Abstract : Introduction/Background: Modified posterior exenteration is procedure performed either during advanced surgical treatment of ovarian cancer and advanced deep infiltrating endometriosis. One of the most severe complications of this procedure is bowel anastomosis leakage. Methodology: Total of 70 patient who underwent modified posterior exenteration (MPE) were enrolled in the study and divided into 2 groups:A: 30 patients treated with laparotomy due to ovarian cancer FIGO IIB – IIICB: 40 patients treated with modified laparoscopic, tailored technique' (ICG, sealing materials) due to deep infiltrating endometriosis (DIE) [at least 1 lesion in colon, only one segment resected] Results: 1) Average distance of bowel anastomosis from the 'Z' line was 90 mm in patients with ovarian cancer vs 75 mm in DIE patients. 2) Average length of resected bowel was similar in both groups. 3) Number of protective stomas was equal: 1 in each group. 4) Bowel anastomosis leakage rate was 10% cases in group A vs 2, 5% in group B. Conclusion: 1) Healing of anastomosis differs between both groups according to different character of the diseases. 2) Possibility to save mesorectum and bowel vascularization in minimal invasive 'tailored' technique in patients with DIE doubtless has significant impact on anastomosis quality – reduces its risk. 3) ICG vascularization control, securing materials usage reduce bowel anastomosis leak risk. 4) Bowel anastomosis distance from the 'Z' line has lower impact on its quality than other analyzed features – significantly lower in patients with DIE.